Pengurusan Fasiliti dan Kualiti Perkhidmatan di Kompleks Kastam, Imigresen dan Kuarantin (CIQ), Johor Bahru, Johor - Shah Izar, Ameer Amzar (Research in Management of Technology and Business, 2021)
Johor Bahru Customs, Immigration and Quarantine Complex (CIQ) is an entrance that connects two countries Malaysia and Singapore. Therefore, the efficiency in managing both facilities and services that has been provide to the customers in the building should be emphasize as it involved the national security issues and impression from outsiders to our country. The objective of this research is to study the facilities provided and customer satisfaction on the quality services and facilities in the CIQ. Both primary and secondary data has been use often in which primary data consist of interview sessions, questionnaire and observation. For secondary data, documents such as regarding previous thesis, articles, newspaper and internet materials has been used. As a result, out of 33 respondents participated in the survey, majority of the respondent perceived that the services and facilities provided are “good”. This building also used a FPMS system in order to record all of the complaints by the users on any default on the building’s facilities.